Final answer:
To multiply and simplify (x-10)(x² - 2x - 7), we expand the product using the distributive property and combine like terms, resulting in the simplified expression x³ - 12x² + 13x + 70.
Step-by-step explanation:
To multiply and simplify the expression (x-10)(x² - 2x - 7), we use the distributive property, also known as the FOIL method for binomials, to expand the product. In this case, we multiply each term in the first expression by each term in the second expression.
- Multiply x by each term in the second expression: x × x² = x³, x × -2x = -2x², x × -7 = -7x.
- Multiply -10 by each term in the second expression: -10 × x² = -10x², -10 × -2x = 20x, -10 × -7 = 70.
Now we combine like terms:
x³ + (-2x² + -10x²) + (-7x + 20x) + 70 = x³ - 12x² + 13x + 70.
Therefore, the simplified result of the multiplication is x³ - 12x² + 13x + 70.